1994
DOI: 10.1128/jb.176.21.6418-6426.1994
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the transcriptional activator VirG of Agrobacterium tumefaciens

Abstract: To find VirG proteins with altered properties, the virG gene was mutagenized. Random chemical mutagenesis of single-stranded DNA containing the Agrobacterium tumefaciens virG gene led with high frequency to the inactivation of the gene. Sequence analysis showed that 29% of the mutants contained a virG gene with one single-base-pair substitution somewhere in the open reading frame. Thirty-nine different mutations that rendered the VirG protein inactive were mapped. Besides these inactive mutants, two mutants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 52 publications
0
30
0
1
Order By: Relevance
“…Identity of or similarity between mutants recovered from the same tumor suggested that these mutants were of clonal origin and had benefited from a selective advantage over wild-type cells in the plant (15,17,19). The positions of the point mutations, each mutation occurring in a different clone, are indicated by the arrows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identity of or similarity between mutants recovered from the same tumor suggested that these mutants were of clonal origin and had benefited from a selective advantage over wild-type cells in the plant (15,17,19). The positions of the point mutations, each mutation occurring in a different clone, are indicated by the arrows.…”
Section: Resultsmentioning
confidence: 99%
“…1B). A previous study (19) on chemical mutagenesis of virG showed that point mutations inactivating protein function were distributed randomly over the coding sequence.…”
Section: Discussionmentioning
confidence: 99%
“…According to the structure predicted by SWISS-MODEL (Guex & Peitsch, 1997;Schwede et al, 2003), a replacement of Asn877 by Ser increases its contact with the site of phosphorylation, Asp875, through hydrogen bonding. Different substitutions at the corresponding positions in VirG (N54D) (Han et al, 1992;Jin et al, 1993;Pazour et al, 1992;Scheeren-Groot et al, 1994), CheB (E58K) (Stewart, 1993) and CheY (N59K, N49R) (Silversmith et al, 2001) also have an activating effect, thereby outlining the importance of this non-conserved residue in the activation of response regulator domains.…”
Section: Discussionmentioning
confidence: 99%
“…A constitutive VirG mutant, VirG(N54D) (191,192,246,374,439), binds to vir box DNA approximately 10-fold more tightly than does wild-type VirG (192). Since the mutation introduces a new negative charge adjacent to the site of phosphorylation, it is thought that this mutation mimics the phosphorylated form of the protein.…”
mentioning
confidence: 99%